2020
DOI: 10.33437/ksusbd.706168
|View full text |Cite
|
Sign up to set email alerts
|

Teknoloji Ediniminin İş Güvensizliği Üzerine Etkisi: Türk Tekstil Sektöründe Bir Alan Çalışması

Abstract: Due to the global changes in trade and economy, firms need to adopt new technologies in their production processes. This brings unending organizational changes and cause resistance and increase the anxiety on losing jobs. Employees think that they can lose their jobs as newer equipment requires less labor. The present study aims to investigate the relationship between technology adoption and job insecurity in a textile manufacturing factory which has adopted a new production infrastructure in Kahramanmaraş. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Job insecurity is the fear of losing a job, influence, or power at the workplace because of new changes that have been introduced. Studies have shown that job insecurity has been one of the reasons why employees have been hesitant or even opposed to the adoption of new technologies in the workplace (Eren et al, 2020). According to Eren et al (2020), research has also shown that job insecurity significantly influences users' intention to adopt new technologies through resistance to change.…”
Section: Job Insecuritymentioning
confidence: 99%
See 1 more Smart Citation
“…Job insecurity is the fear of losing a job, influence, or power at the workplace because of new changes that have been introduced. Studies have shown that job insecurity has been one of the reasons why employees have been hesitant or even opposed to the adoption of new technologies in the workplace (Eren et al, 2020). According to Eren et al (2020), research has also shown that job insecurity significantly influences users' intention to adopt new technologies through resistance to change.…”
Section: Job Insecuritymentioning
confidence: 99%
“…Studies have shown that job insecurity has been one of the reasons why employees have been hesitant or even opposed to the adoption of new technologies in the workplace (Eren et al, 2020). According to Eren et al (2020), research has also shown that job insecurity significantly influences users' intention to adopt new technologies through resistance to change. For instance, T. Nam (2019) indicated that job insecurity triggers resistance to change and a sense of withdrawal response among employees.…”
Section: Job Insecuritymentioning
confidence: 99%